Relação teoria–pratica no processo ensino-aprendizagem na criação de coleção de moda em projeto de extensão universitária (ModaPalavra e-periódico, 2013)
This paper presents the teaching mediation in the teaching-learning process and the relationship between theory and practice in performing the three steps of the university extension project: idea and creation, development and the presentation of a collection fashion show. Developed in a partnership with the teaching staff and students of the Course of Fashion, Design and Styling Centers of UFPI and Productive Garment centers assisted by SEMDEC, this work set in a rich exchange of knowledge among its participants.
Keywords: mediation; university extension; fashion production